NEPHROTIC EDEMATA: WHY THERAPY IS NOT ALWAYS EFFECTIVE? - A. M. Rivkin (Педиатрическая фармакология)
The article is dedicated to nephrotic syndromes in children. It is not difficult to diagnose; however, numerous variants of the clinical course and different intensity of manifestations in patients pose problems when selecting either a remission-inducing or symptomatic therapy. As practice shows, proper correction of edema syndromes is especially complicated. The article reviews the main literature data on various development mechanisms of nephrotic edemata and approaches to therapeutic measures. It gives careful consideration to the method of performing infusion therapy and diuretic prescription in relation to peculiarities of the edema development mechanism and condition of renal tubulointerstitium.